Modeling and Experimental Investigation of Laminar Ceiling Air Distribution System for Operating Room in Merjan Teaching Hospital - Abed, Isam A.; Hamza, Ruqaia A. (ITB Journal Publisher, LPPM ITB, 2018)
Room air distribution in operating rooms is critical to successful surgical treatment. The present study investigated the effects of the location of the air supply and exhaust grills on the air movement and air parameters inside an operating room. This paper presents an experimental and numerical analysis of air distribution in the operating room. The experimental work was conducted in an operating room in Merjan Teaching Hospital in the city of Babylon. Air was supplied from one square plenum box located in the middle of the ceiling, while air was exhausted through eight grills: large exhaust grills in the four upper corners and small exhaust grills in the four lower corners. In the theoretical work, a model of the operating room was developed and two cases were analyzed using the FLUEN 6.3.26 software program. The first case included all eight exhaust grills, while the second case included only the four lower exhaust grills. The ceiling system gave good ventilation for air distribution inside the operating room. There was no clear effect of the small exhaust grills located in the upper corners of the operating room. The height of the ceiling room is an effective factor in air distribution.